Polimorfizem genov za ß-laktoglobulin in alfaS1-kazein paške ovce - Ivanković, Ante (Acta agriculturae Slovenica, 2004)
Polymorphisms of lactoprotein genes have a significant effect on technological properties of milk. In spite of the fact that literature data on the impact of lactoprotein variants on cheese making properties are sometimes contradictory, the information about the lactoprotein genotypes becomes important in selection programs in order to improve frequency of favourable alleles for technological properties of milk. The main product of the Pag Islad Sheep is milk, which is mainly used for manufacturinh of well known Pag Cheese. The improvement of cheese making properties of the Pag Island Sheep milk would contribute significantly to the rentability of the breed. In order to estimate the frequency of alleles contributing to technological properties of milk, we genotyped ß-lactoglobulin and alfas1-casein loci of 40 Pag Island Sheep. Genotyping was performed using PCR followed by restriction analysis. At the ß-lactoglobulin locus alleles A and B (0.5375; 0.4625) were found whereas at the alfas1-casein locus genotyping of alleles A in D (0.0875; 0.1340) was performed. According to the literaure data, we can conclude that allele frequencies at -lactoglobulin and s1-casein locus in the population of Pag Island Sheep are not optimal for cheese making properties of milk. Application of molecular techniques would enable relatively rapid improvement of allelic frequencies towards technologically favourable alleles. This would also improve economical parameters of milk production with Pag Island Sheep breed, which is only known for special Pag cheese.
Keywords: ovce; pasme; Pag; mleko; laktoglobulini; kazein; molekularna genetika; polimorfizem